Online oral health information seeking experience and knowledge, attitudes and practices of oral health among iranian medical students: an online survey - Peivand Bastani; Mohammad Amin Bahrami; Kostas Kapellas; Alireza Yusefi; Giampiero Rossi-Fedele (BMC, 2022)
Abstract Background The internet is increasingly used as a source of health information. This study aimed to explore the online oral health information seeking experience, to determine the knowledge, attitudes and practices (KAP) of oral health, and to investigate the associations between online oral health information seeking experience and oral health KAP of participants. Methods A cross-sectional online survey was conducted. Three hundred and ninety-five university students participated in the study. Required data were gathered using two valid questionnaires eHIQ (e-Health Information Questionnaire) and Oral Health Knowledge, Attitude and Behavior Questionnaire. eHIQ was a 2-part instrument with 37 items. eHIQ-Part 1 includes 11 items related to general views of using the internet in relation to health. eHIQ-Part 2 includes 26 items related to the consequences of using specific health-related online sources. The second questionnaire includes 30 items as a combination of multiple-choice and yes/no type questions. The data were analyzed using the statistical analysis software SPSS version 20. Mean scores, standard deviation, and frequency distribution were obtained. Independent T-test, correlation coefficients and analysis of variance (ANOVA) were used in the analysis. Results Participants had good KAP of oral health. The between-group differences tests showed that oral health knowledge and attitudes were significantly different between gender and years of study groups, but the differences of oral health practices were significant only based on years of study. Participants had moderate scores regarding all sub-scales of eHIQ-Parts 1 and 2. Findings revealed that online oral health information seeking behavior was associated with oral health KAP (p < 0.05). Conclusion According to the results the general views of using the internet in relation to health and the consequences of using specific health-related online sources were in a moderate level among the participants. Such results can emphasize the need for more planning, education and empowerment of the population`s health literacy. The present study also provides good insights for the latter and has practical and policy implications besides its research values.